2014
DOI: 10.1155/2014/840852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbubble Size on Ultrasound-Mediated Gene Transfection in Auditory Cells

Abstract: Gene therapy for sensorineural hearing loss has recently been used to insert genes encoding functional proteins to preserve, protect, or even regenerate hair cells in the inner ear. Our previous study demonstrated a microbubble- (MB-)facilitated ultrasound (US) technique for delivering therapeutic medication to the inner ear. The present study investigated whether MB-US techniques help to enhance the efficiency of gene transfection by means of cationic liposomes on HEI-OC1 auditory cells and whether MBs of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(43 reference statements)
1
21
0
Order By: Relevance
“…Previous studies showed that cavitation behavior and stability of microbubbles mainly depend on microbubble size [43, 44]. The natural frequency of microbubbles depends on their diameter [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that cavitation behavior and stability of microbubbles mainly depend on microbubble size [43, 44]. The natural frequency of microbubbles depends on their diameter [45].…”
Section: Discussionmentioning
confidence: 99%
“…This technique not only increases the permeability of the RWM and facilitates drug delivery into the inner ear, but the preliminary results also show no resulting damage to the integrity of the RWM or deterioration of the hearing thresholds, as assessed by auditory brainstem responses. Furthermore, in 2014, we demonstrated that USMBs were effective at facilitating gene transfer to auditory cells in vitro (Liao et al, 2014) and that the size-dependent MB oscillation behavior in the presence of US plays a role in enhancing gene transfer. In addition, dexamethasone delivery to the round window of animals with the aid of USMBs has a greater efficacy in protecting the inner ear from noise-exposed injury when compared to a simple soaking with the drug (Shih et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…The 600–650 nanometer sized droplets would be expected to result in microbubbles that were at least 3–4 microns in size (7), and perhaps slightly larger due to inward diffusing dissolved nitrogen gas within the blood stream. Even at these sizes though, they would still be expected to pass freely through the myocardial capillaries (13) while also being more resistant to destruction than smaller sized perfluorocarbon microbubbles (14). Intravenously infused commercially available microbubbles within the capillaries would not be visualized at this high mechanical index and frame rate, since capillary blood replenishment with intravenously infused C3 microbubbles would not be expected at this frame speed (10).…”
Section: Discussionmentioning
confidence: 99%